Early and Long-Term Outcomes of Surgical Treatment of Ebstein’s Anomaly - Silva,Guilherme Viotto Rodrigues da (2019)
Abstract Objective: This study aimed to evaluate Ebstein’s anomaly surgical correction and its early and long-term outcomes. Methods: A retrospective analysis of 62 consecutive patients who underwent surgical repair of Ebstein’s anomaly in our institution from January 2000 to July 2016. The following long-term outcomes were evaluated: survival, reoperations, tricuspid regurgitation, and postoperative right ventricular dysfunction. Results: Valve repair was performed in 46 (74.2%) patients - 12 of them using the Da Silva cone reconstruction; tricuspid valve replacement was performed in 11 (17.7%) patients; univentricular palliation in one (1.6%) patient; and the one and a half ventricle repair in four (6.5%) patients. The patients’ mean age at the time of surgery was 20.5±14.9 years, and 46.8% of them were male. The mean follow-up time was 8.8±6 years. The 30-day mortality rate was 8.06% and the one and 10-year survival rates were 91.9% both. Eleven (17.7%) of the 62 patients required late reoperation due to tricuspid regurgitation, in an average time of 7.1±4.9 years after the first procedure. Conclusion: In our experience, the long-term results of the surgical treatment of Ebstein's anomaly demonstrate an acceptable survival rate and a low incidence of reinterventions.